Factores personales y laborales que influyen en la motivación de las tutoras en el trabajo con los niños de la cuna Materno Infantil “Raúl Edmundo Haya y Cárdenas” de la junta de participación social en el distrito de Moche – Trujillo: 2016. - Olguín Guzmán, Idiana Saidy (2016)
This thesis was done in order to explain how personal and occupational factors influence the motivation of the tutors working with Children Cradle Mother and Child "REHyC" Board of Social Participation in the District of Moche - Trujillo : 2016. It was considered the type of applied research, based on an explanatory design, and the sample universe consisted of 13 tutors, which worked with applying the methods and techniques of quantitative and qualitative research. From the results it can be deduced that this institution there are problems and dissatisfaction with personal development, little training, poor interpersonal relationships, low level of communication and poor remuneration, incentives and recognition of labor rights affecting motivation, performance and generates job dissatisfaction. Besides inadequate organizational climate, it encourages non-practice of corporate values, poor expectations, beliefs, norms and shared and borne tures of this Child Cuna practices. Finally we believe that this institution must implement effective programs to improve motivation and job satisfaction. Effective programs can also have a positive impact on morale and productivity of the tutors.